Designing and evaluating a novel mobile application for Helping Babies Breathe skills retention in Uganda: comparative study protocol - Shaun K Morris; Hasan Shamsh Merali; Natalie Hoi-Man Chan; Niraj Mistry; Ryan Kealey; Douglas Campbell; Santorino Data (BMJ Paediatrics Open)
Introduction Over 600 000 newborns die each year of intrapartum-related events, many of which are preventable in the presence of skilled birth attendants. Helping Babies Breathe (HBB) is a neonatal resuscitation training programme designed for low-resource settings that can reduce both early neonatal mortality and stillbirths. However, as in other similar educational programmes, knowledge and skill retention deteriorate over time. This trend may be counteracted by strategies such as regular simulated exercises. In this study, a mobile application (app) ‘HBB Prompt’ will be developed to assist providers in retaining HBB knowledge and skills.Methods and analysis This is a comparative study in Uganda with two phases: an app development phase and an assessment phase. In the first phase, HBB trainers and providers will explore barriers and facilitators to enhance learning and maintenance of HBB skills and knowledge through focus group discussions (FGDs). The FGDs are designed with a human factors perspective, enabling collection of relevant data for the prototype version of HBB Prompt. The app will then undergo usability and feasibility testing through FGDs and simulations. In the second phase, a minimum of 10 healthcare workers from two district hospitals will receive HBB training. Only the intervention hospital will have access to HBB Prompt. All participants will be asked to practise HBB skills every shift and record this in a logbook. In the intervention site, app usage data will also be collected. The primary outcome will be comparing skills retention 12 months after training, as determined by Objective Structured Clinical Examination B scores.Ethics and dissemination This study received ethics approval from The Hospital for Sick Children and Mbarara University of Science and Technology. The authors plan to publish all relevant findings from this study in peer-reviewed journals.Trial registration number NCT03577054